PENINGKATAN KINERJA GURU MELALUI PARADIGMA KEPEMIMPINAN KEPALA SEKOLAH - Habibi, Ilham (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
The purpose of writing this paper is to find out whether the principal's leadership style plays an important role in improving the performance of teachers who are none other than members or staff themselves, in practice, the teacher in carrying out tasks is still not optimal, one of the causes is the leadership style of a principals who are considered less effective so that teachers are also reluctant to carry out their duties wholeheartedly, therefore, the principal seems to understand and adjust his leadership style with staff and members so as to create a sense of comfort and goals desired by the school will be achieved more effectively and efficiently. The results of this paper also state that the principal's leadership style is very important in increasing or decreasing teacher performance, if good, then the teacher will be even more eager to do work and tend to be proud of his work, if bad, then the teacher will not be serious really or not wholeheartedly in carrying out their duties at school, and that also becomes an obstacle for the principal to realize the school he wants. If the leadership style of the school principal is good, then the changes felt by all groups in the school will be positive as well so that an environment can be created to encourage the achievement of the goals set by the school.Keywords: Leadership style, Principal, Teacher performance.